Combustion features from short-lived intermittent occupation at a 1300-year-old Coast Salish rock shelter, British Columbia: The microstratigraphic data. (February 2019) - Toffolo, Michael B.; Ritchie, Morgan; Sellers, Ian; Morin, Jesse; Lyons, Natasha; Caldwell, Megan; Albert, Rosa M.; Letham, Bryn; Berna, Francesco
Abstract: Short-lived occupation sites are the most common component of the archaeological record at the regional scale level, but are often underrepresented due to their low amount of cultural material and greater visibility of larger sites. Small ephemeral sites can however provide unique information regarding land and resource use, travel routes, harvesting practices, group size, food processing, ceremonial activities and chronology of occupation, especially in pre-urban societies. One of the most prominent proxies for short-lived occupation is combustion features, defined as accumulations of ash, burnt bones, heat-altered sediments and stone tools. These features provide insights into behavioral evolution, food consumption, settlement patterns and foraging strategies, and the preservation of the archaeological record. To obtain this information, a microscopic level of investigation is required in order to address the chemical and mineralogical characteristics of combustion features. We deployed such kind of microarchaeological approach to the study of combustion features at the DjRr-4 rock shelter along the Indian River, British Columbia, settled by Coast Salish peoples at least 1300 years ago. Using a combination of micromorphology of sediments, phytolith and diatom analysis, paleobotany, zooarchaeology, lithic analysis and radiocarbon dating, we were able to show that the shelter was used intermittently over short time spans as a base camp for hunting, likely as a station along a trail that connected the coast to interior regions. Our results are consistent with chronological data for the region and with the adoption of bow and arrow by Coast Salish peoples. Highlights: A Coast Salish rock shelter was surveyed in the Indian River Valley, BC, Canada. Samples for microarchaeological analyses were collected from a 40 × 40 cm test. Micromorphology shows the occurrence of at least four intact combustion features. Botanical and faunal analyses indicate exploitation of local resources (hunting). Earliest occupation contemporary with use of bow and arrow by Coast Salish peoples.